South Sumatra's Opportunities in Accessing ASEAN Economic Community (AEC) - Syuryansyah, Syuryansyah; Amalia, Ridha; Farid, Miftah (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
This study aims to explore the role of local government policies in South Sumatra in accessing and enhancing economic cooperation with countries in the Southeast Asian region, particularly within the framework of the ASEAN Economic Community (AEC). Although economic cooperation among ASEAN nations has advanced significantly over recent decades, there is still untapped potential by local governments in Indonesia, including South Sumatra, in contributing to regional economic integration. The research investigates how local economic policies in South Sumatra can strengthen its involvement in the AEC, with a focus on trade, investment, and infrastructure development that fosters connectivity among ASEAN nations. A qualitative approach with policy analysis is employed to understand the strategies adopted by the South Sumatra government in promoting economic collaboration with ASEAN countries. The findings are expected to identify crucial factors influencing the success or failure of accessing ASEAN market and offer recommendations for improving coordination between central and local governments to enhance South Sumatra's role in the ASEAN economic network. Ultimately, the study aims to contribute to the development of more effective regional economic policies that support regional integration and elevate South Sumatra’s standing in the ASEAN economic landscape.